Functional roles of norCB in Pseudomonas aeruginosa ATCC 9027 under aerobic conditions. (25th September 2019) - Zhou, Gang; Wang, Ying‐Si; Peng, Hong; Shen, Peng‐Fei; Xie, Xiao‐Bao; Shi, Qing‐Shan
Abstract: Nitric oxide (NO) reductase (NorCB) of Pseudomonas aeruginosa is an essential enzyme that metabolizes NO and alleviates anaerobic NO toxicity during denitrification processes under anaerobic conditions. However, the molecular functions of norCB in the presence of oxygen are poorly understood. This study utilized norCB knockout from P. aeruginosa ATCC 9027 to analyze the resulting phenotypic changes of ΔnorCB in comparison to the wild‐type parental strain (WT) and the complementary strain ( ΔnorCB ‐com). The results demonstrated an increase in planktonic growth and biofilm formation by ΔnorCB compared to WT and ΔnorCB ‐com in the presence of isothiazolones under aerobic conditions. Deletion of norCB led to increased swimming ability and decreased pyocyanin production. Inactivation of norCB also led to an increase of cellular H2 O2 concentration due to decreased activity of its catalases. In addition, the deletion of norCB also influenced the relative expressions of several other genes, including norD, nirS, hmgA, and hpd . These findings provide preliminary evidence that norCB in P. aeruginosa plays an essential role in bacterial life process under aerobic conditions and improves the application of denitrification in the next step.